Impact of pin tool designs on the mechanical properties and microstructure of aluminum alloys AA7075- AA6061. (3rd October 2021) - Batool, Adeeba; Anjum, Nazeer Ahmad; Khan, Muhammad Yasir
ABSTRACT: In this work, Friction Stir Welding (FSW) is used to study the impact of different pin tool geometries on hardness, microstructure, and tensile strength of welded AA6061 and AA7075 butt joints. H13 steel-tool including three distinct pin geometries, i.e. threaded cylindrical (THC), straight cylindrical (SC), and tapered cylindrical (TAC) are used for welding. The welds were produced using a spindle speed of 1800 rpm and welding speed (traverse speed) of 15 mm/min by a customized clamping system. As shown by the hardness test, the welded sample using the threaded pin tool geometry produces more hardened joints than other geometries of the pin tools. As analyzed by the tensile strength experiment performed on the Universal Testing Machine (UTM), the samples welded by threaded pin give higher ultimate tensile strength, i.e. 282 MPa compared to other tool geometries. A fine grain structure was also observed in the nugget zone of welded joints obtained by threaded pin.